Lignin and cellulose extraction from coconut shell using ionic liquids / Siti Mastura Mohamad Zakaria - Siti Mastura , Mohamad Zakaria (2017)
Coconut shell, a natural lignocellulosic biomass, is available in high amount as an agriculture waste in many countries. To utilize this biomass and convert it into high-value products, there is a need to find alternative solvents that efficiently dissolve lignocellulosic biomass. Recently, ionic liquids (ILs) have attracted much attention due to its unique characteristics; such as negligible vapor pressure, non-flammability, and a low melting point. It has been demonstrated that ILs can dissolve biomass partially or completely, depending on the type of biomass. In this study, we have investigated protic and aprotic ionic liquids as pretreatment solvents for the dissolution of coconut shell. The extraction efficiency was greatly influenced by temperature, duration time, particle size, and types of cations and anions of the ionic liquids. The effects of pretreatment variables on the chemical composition, surface morphology, crystallinity, and thermal stability of regenerated lignin and cellulose from coconut shell were investigated. The solubility tests showed that aprotic ionic liquids have good solubility performance (7 wt %) compared to protic ionic liquids (1 wt %). Thus, a series of aprotic ionic liquids (AILs), [Bmim][Ace], [BMIM]Cl, [Emim][Ace], and [Emim]Cl, were chosen and used in the dissolution and regeneration process of coconut shell. The optimum process pretreatment for dissolution was at 110°C and the particle size of ranges are from 10 - 63 μm. The results indicated that the dissolution of coconut shell (up to 70 mg of coconut shell per g of solvent) were obtained in aprotic ionic liquids at 110°C (6 h) and 150°C (2 h). At 150°C, the regenerated lignin from precipitation of [Emim][Ace] was 10.3 %, while the regenerated cellulose was 70 %. Increasing the temperature caused the regenerated lignin to increase, while the regenerated cellulose was decrease. Among the ILs explored, imidazolium acetate is the best IL to regenerate lignin, whereas imidazolium chloride is suitable to regenerate cellulose. The structural and chemical changes of the raw coconut shell and regenerated fractions (lignin and cellulose) properties were characterized by Fourier transform infra-red (FTIR) spectroscopy, thermogravimetric analysis (TGA), field emission scanning electron microscopy (FESEM), differential scanning calorimetry (DSC), X-ray diffraction (XRD) analysis, and proton nuclear magnetic resonance (1H NMR). Recycling and reuse of ILs can develop cost-friendly and green technique process for utilization and fractionation of biomass. The aprotic ionic liquids, [Bmim]Cl, [Bmim][Ace], [Emim][Ace], and [Emim] Cl were recovered and reused up to four times with 90 % recovery. 1H NMR spectra showed no structural changes which indicate no side products were formed during pretreatment process in the recycled aprotic ionic liquids. Thus, it shows that ionic liquids can be environmentally friendly pretreatment solvents to dissolve and fractionate lignin and cellulose.